Focused lung ultrasound to predict respiratory failure in patients with symptoms of COVID-19: a multicentre prospective cohort study - Søren Helbo Skaarup; Rasmus Aagaard; Stig Holm Ovesen; Jesper Weile; Hans Kirkegaard; Caroline Espersen; Mats Christian Højbjerg Lassen; Kristoffer Grundtvig Skaarup; Stefan Posth; Christian B. Laursen; Ask Bock; Michael Dan Arvig; et al. (ERJ Open Research, 2022)
Background In this study we aimed to assess if a focused lung ultrasound examination predicts the need for mechanical ventilation, admission to an intensive care unit, high-flow oxygen treatment, death from COVID-19 within 30 days and 30-day all-cause mortality in patients with clinical suspicion of COVID-19 or PCR-verified SARS-CoV-2 infection. Methods A multicentre prospective cohort trial was performed. Film clips from focused lung ultrasound examinations were recorded and rated by blinded observers using different scoring systems. A prediction model was built and used to test relationship between lung ultrasound scores and clinical outcomes. Diagnostic performance of scoring systems was analysed. Results A total of 3889 film clips of 398 patients were analysed. Patients who had any of the outcomes of interest had a significantly higher ultrasound score than those who did not. Multivariable logistic regression analyses showed that lung ultrasound predicts mechanical ventilation (relative risk 2.44, 95% CI 1.32–5.52), admission to intensive care (relative risk 2.55, 95% CI 1.41–54.59) and high-flow oxygen treatment (relative risk 1.95, 95% CI 1.5–2.53) but not survival when adjusting for sex, age and relevant comorbidity. There was no diagnostic difference in area under the receiver operating characteristic curve between a scoring system using only anterolateral thorax zones and a scoring system that also included dorsal zones. Conclusion Focused lung ultrasound in patients with clinical suspicion of COVID-19 predicts respiratory failure requiring mechanical ventilation, admission to intensive care units and the need for high-flow oxygen treatment. Thus, focused lung ultrasound may be used to risk stratify patients with COVID-19 symptoms.